Health education and worker quality of life - Paula, Maria Angela Boccara de (2015)
Quality of life is a multifaceted concept intrinsically related to the world around us, has been approached under different "looks", being interdisciplinary. This article discusses worker health education aspects that can facilitate the improvement of quality of life considering: the man and the work and the possibilities and opportunities that education offer to contribute to the living better process and with quality. This is not to exhaust the subject, which is broad and complex, but reflect on those opportunities that can be performed simply and without high costs, but with important results when health education is performed continuous and procedurally.